2017
DOI: 10.1017/prp.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Schedule Control, Work Interference With Family, and Emotional Exhaustion: A Reciprocal Moderated Mediation Model

Abstract: T he current research drew upon the resource perspective (Grzywacz & Marks, 2000;ten Brummelhuis & Bakker, 2012) and firstly focused on the reciprocal mediation relationship between schedule control, work interference with family (WIF) and emotional exhaustion. First, the present study proposed that WIF mediates the negative relationship between schedule control and emotional exhaustion, and emotional exhaustion also mediates the negative relationship between schedule control and WIF. Second, family time adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 43 publications
5
9
0
Order By: Relevance
“…The findings of the present study emphasize the important role played by the balance between work and private life in conveying not only the detrimental effects of job demands but also the alleviating effects of job resources on employee fatigue. They support previous propositions that the impairment of private life acts as a key mechanism linking work conditions to EE and burnout [ 16 , 27 , 28 ]. As suggested by [ 16 ], the present results suggest that WLC should be integrated into the job demands resources model as a central mediator through which both work demands and work resources affect the health of the employees.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of the present study emphasize the important role played by the balance between work and private life in conveying not only the detrimental effects of job demands but also the alleviating effects of job resources on employee fatigue. They support previous propositions that the impairment of private life acts as a key mechanism linking work conditions to EE and burnout [ 16 , 27 , 28 ]. As suggested by [ 16 ], the present results suggest that WLC should be integrated into the job demands resources model as a central mediator through which both work demands and work resources affect the health of the employees.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, hypothesis H2 postulated that temporal latitude mitigates EE not only directly but also indirectly by reducing the work-related impairment of private life. As expected, the model found a significant negative, indirect effect between WF and EE, which was slightly higher than in a comparable study (β = −0.08 [ 27 ]).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Results from this study are in line with previous research. Based on an occupational cohort with one year follow-up, a study found that WLI mediated the relationship between a general measure of WTC and emotional exhaustion ( 29 ). Our findings support these results but additionally highlight several points: (i) the two sub-dimensions of WTC differed consistently in size; (ii) indirect effect estimates varied for different health outcomes; (iii) reciprocal mediation, direct and reversed direct effects explained a smaller part of the effect; and (iv) effects remained robust even after controlling for a number of covariates.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study based on a sample of workers in the healthcare sector concluded that WLI did play a mediating role in the relation between WTC and emotional exhaustion ( 29 ). The author also found evidence that emotional exhaustion mediated effects of WTC on WLI, meaning WTC affected emotional exhaustion which in turn influenced WLI.…”
mentioning
confidence: 99%